2018
DOI: 10.1080/2331205x.2018.1560641
|View full text |Cite
|
Sign up to set email alerts
|

Community-based vision health screening with on-site definitive exams: Design and outcomes

Abstract: In the U.S., the prevalence of blindness is expected to double by 2050 and as many half of those with blinding eye disease are unaware of their diagnosis. Screening for vision health in the community setting may offer a key strategy to address the rising trend avoidable vision loss. However, problems with excessive referrals and low compliance with these referrals (often <50%) undermine the effectiveness of vision screening programs. We investigated the outcomes of a modified vision screening program design. K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In Portland, Oregon, Brinks et al showed that partnering with community organizations could provide resources to manage screenings, scheduling, provision of spectacles and referral to clinical eye care, among other tasks. 37 Community organizations could be a source of personnel to maintain the patient navigator role. In student-run clinics or screening programs at academic centers, the patient navigator role could be handled by interested medical or public health students.…”
Section: Discussionmentioning
confidence: 99%
“…In Portland, Oregon, Brinks et al showed that partnering with community organizations could provide resources to manage screenings, scheduling, provision of spectacles and referral to clinical eye care, among other tasks. 37 Community organizations could be a source of personnel to maintain the patient navigator role. In student-run clinics or screening programs at academic centers, the patient navigator role could be handled by interested medical or public health students.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to health education, public health officials created resources like the Manhattan Screening Project to promote vision screenings. Vision screenings in community settings can have a direct impact on the prevalence of vision loss and blindness as they allow patients and doctors to identify the early beginnings of diseases like glaucoma, diabetic retinopathy, and macular degeneration [ 9 ]. Therefore, the objective of this analysis is to understand and characterize the obstacles encountered by patients in accessing eye care services, as determined by existing literature.…”
Section: Introductionmentioning
confidence: 99%
“…Most traditional models of vision screening in the community rely on a visual acuity chart test with a pinhole to identify people who should be referred for disease-related visual impairment. [14][15][16] However, such models have inherent limitations. For instance, although the pinhole visual acuity test is commonly thought to be a quick measure of vision level and can be done by a nurse or layperson, it has poor reliability and repeatability, 17,18 with inconsis tencies in doc umentation of results among testers.…”
Section: Introductionmentioning
confidence: 99%
“…19 Importantly, sub optimal pinhole visual acuity results are only an estimate to indicate potential disease-related visual impairment but do not definitively confirm the presence of eye disease, thus often resulting in a high proportion of unnecessary false positive referrals. 18,20,21 A second model used in some countries is to add retinal photography 22,23 or other methods such as air-puff tonometry (for intraocular pressure measurement), 14 to identify eye disease. In particular, adding retinal photography offers the advantage of ascertaining the presence of disease by providing direct visualisation of the fundus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation